Development and Optimization of an Ultrasound-Assisted Extraction Apparatus with Integrated Advanced Features for Enhanced Essential Oil Production - Fatmasari, Diyah; Widyawati, Melyana Nurul; Amartha, Tecky Afifah Santy; Fathonah, Yayuk; Aquarista, Nita; Amalia, Dhanty Nurul (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
The development of essential oil extraction techniques has seen significant advancements with the introduction of Ultrasound-Assisted Extraction (UAE) technology. UAE is known for its ability to accelerate chemical processes and improve the efficiency of essential oil extraction. However, to achieve optimal extraction quality and yield, precise control over various process parameters is required. This study focuses on enhancing the UAE extraction process by integrating modified features, including a temperature sensor, speed sensor, frequency regulator, temperature controller, stirrer, and cooler, into the extraction apparatus. Objective of this research is to develop a UAE-based extraction apparatus with advanced features that optimize the pre-treatment extraction process of essential oils. The research employs a Research and Development (R&D) approach to design and develop the UAE-based extraction apparatus. The apparatus is then tested to evaluate its performance in optimizing the extraction process. Experimental trials are conducted to assess the impact of each feature on the efficiency and quality of the extracted essential oils. The integration of the temperature sensor, speed sensor, frequency regulator, temperature controller, stirrer, and cooler allowed for better control over the extraction conditions, leading to higher yield and improved quality of the essential oils. The apparatus demonstrated its ability to consistently produce essential oils with higher purity and active ingredient concentrations compared to conventional methods. In conclusion, the development of the modified UAE-based extraction apparatus proves to be an effective solution for optimizing the essential oil extraction process